Elementos visuais no design de interface: uma análise da usabilidade e jogabilidade de jogos digitais para consoles portáteis - AQUINO, Ana Carolina Generoso de (2020)
The relevance of the digital gaming market grows exponentially, as well as its means of application inside and outside the ludic aspects. Digital games have as main form of connection with the user, their visual interfaces, which oversee displaying the necessary information so that the interaction between player and system occurs. However, it is still recent the exploration of this area within the academic research, which focus within the analysis and evaluation of such interfaces and their correlation with the user experience. In addition, digital games have several means of reproduction and, consequently, different ways in which the game interfaces can be modified. Thus, the focus of this research is on portable consoles, a cross between mobile devices and fixed consoles, which have become popular over time, but does not have a great acceptance by the consumer public. Therefore, the objective of this research is to analyze the structuring of the visual elements in the interface design of digital games for portable consoles. Based on the reflection of the visual elements in digital games for handheld consoles through an analysis tool, a comparative study between results obtained through the tool and heuristics was performed, as well as a cross examination between these data with usability and gameplay tests performed with users with different levels of expertise with digital games. From the methodological procedures adopted, a set of 16 recommendations was created for structuring the interactive visual elements in the design of the digital game interface for handheld consoles, using the Delphi Method.